2009
DOI: 10.1097/hjh.0b013e3283310ece
|View full text |Cite
|
Sign up to set email alerts
|

Muscle sympathetic nervous activity in depressed patients before and after treatment with sertraline

Abstract: Moderate-to-severe depression is associated with increased MSNA. Sertraline treatment reduces MSNA at rest and during mental challenge in depressed patients, which may have prognostic implications in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 59 publications
1
39
0
3
Order By: Relevance
“…Anti-depressants, in particular, have been shown to dramatically inhibit central sympathetic outflow and reduce MSNA (Esler et al, 1991; Scalco et al, 2009). The reduction in MSNA, while not statistically significant, appeared to be even greater with the combination of MS disease modifying therapy and these medications compared to disease modifying therapy alone (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-depressants, in particular, have been shown to dramatically inhibit central sympathetic outflow and reduce MSNA (Esler et al, 1991; Scalco et al, 2009). The reduction in MSNA, while not statistically significant, appeared to be even greater with the combination of MS disease modifying therapy and these medications compared to disease modifying therapy alone (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of major depression were shown to be associated with cardiovascular disease and myocardial infarction (Musselman, Evans, & Nemeroff, 1998). Sympathetic muscle activity in depression patients was higher than in normal subjects, and the muscle activity augmentation effect was reduced after treatment with the antidepressant sertraline (Scalco et al, 2009). Conversely, some data have indicated that depression facilitates the parasympathetic division but not the sympathetic division (Lechin et al, 1995a,b).…”
mentioning
confidence: 99%
“…Other investigations have found local SNS activity to be associated with depression. Muscle SNS activity was elevated in major depression disorder (MDD) patients that had high depression symptoms compared with MDD patients with lower depression symptoms (10). Despite the lack of relationship between depression and catecholamines in the present study, observed differences in leukocyte β-AR sensitivity in relation to major depression may illustrate that functional measures of SNS may be important in depression studies for examining SNS activation.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms observations from other studies that also did not find a correspondence between depression as a continuous variable and β-AR sensitivity (24). However, some studies have found non-linear relationships between sympathetic activity and depression symptoms (10), 13). For example, the overall rate of spillover of NE to plasma did not differ between the healthy subjects and the patients with major depressive disorder (MDD); whereas the rate of NE spillover to plasma followed a bimodal distribution with a subset of MDD patients having very high sympathetic nervous activity, including sympathetic outflow to the heart (13).…”
Section: Discussionmentioning
confidence: 99%